2013
DOI: 10.1016/j.immuni.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor STAT-1 Couples Macrophage Synthesis of 25-Hydroxycholesterol to the Interferon Antiviral Response

Abstract: SummaryRecent studies suggest that the sterol metabolic network participates in the interferon (IFN) antiviral response. However, the molecular mechanisms linking IFN with the sterol network and the identity of sterol mediators remain unknown. Here we report a cellular antiviral role for macrophage production of 25-hydroxycholesterol (cholest-5-en-3β,25-diol, 25HC) as a component of the sterol metabolic network linked to the IFN response via Stat1. By utilizing quantitative metabolome profiling of all naturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
462
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(505 citation statements)
references
References 44 publications
30
462
0
1
Order By: Relevance
“…Although two recent independent studies demonstrated the broad antiviral activity of 25OHC, the mechanism by which 25OHC suppresses viral infection is still unclear (11,12,59). We demonstrate that 25OHC significantly alters important plasma membrane lipid species and activates the ISR, both of which may contribute to the antiviral activity of 25OHC.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 61%
See 2 more Smart Citations
“…Although two recent independent studies demonstrated the broad antiviral activity of 25OHC, the mechanism by which 25OHC suppresses viral infection is still unclear (11,12,59). We demonstrate that 25OHC significantly alters important plasma membrane lipid species and activates the ISR, both of which may contribute to the antiviral activity of 25OHC.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 61%
“…MCMV Infection Stimulates 25OHC Production and Induces Stress Response Gene Transcription-Ch25h is an interferonstimulated gene, and two recent independent publications demonstrated that CH25H and its product 25OHC have broad antiviral activity (11,12). To determine whether the concentrations of 25OHC produced during viral infections were capable of inducing ISR genes, we infected BMDMs with MCMV.…”
Section: Ohc Suppresses Srebps Activates Lxrs and Induces Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…25-Hydroxycholesterol (25-HC) is an oxysterol that displays potent antiviral activity (44,45). Additionally, Ch25h, the gene encoding cholesterol 25-hydroxylase, which controls the production of 25-HC, is classified as an ISG (46).…”
Section: Atf3 Directly Regulates a Subset Of Isgs In Response To Ifn-bmentioning
confidence: 99%
“…Cholesterol 25-hydroxylase (encoded by Ch25h) catalyzes the formation of 25-HC during cholesterol metabolism, and ATF3 was previously found to directly regulate Ch25h expression (47). Additionally, separate studies have characterized Ch25h as an ISG, and 25-HC has been shown to elicit broad antiviral functions (44,45). In this study, we show, to our knowledge for the first time, that ATF3 can regulate the expression of Ch25h following IFN signaling, a mechanism that is likely important for maintaining an appropriate immune response to viruses.…”
Section: Isgs Similar To Atf3mentioning
confidence: 99%